Targeting angiogenesis in advanced cervical cancer - Eskander, Ramez N. (SAGE Publications, 2014)
Patients with advanced stage or recurrent cervical cancer represent a population with limited chemotherapeutic options. More specifically, patients with recurrent disease have a poor salvage rate, with a 5-year survival rate of less than 10%. This year, the first prospective phase III clinical trial exploring the anti-angiogenic agent, bevacizumab, was published, meeting its primary endpoint, with a significant improvement in overall survival. As such, a review of anti-angiogenic therapy in the treatment of this disease is warranted.